2021
DOI: 10.3390/biom11020149
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Periodontitis in a Patient with Combined Classical and Periodontal Ehlers–Danlos Syndrome

Abstract: We report an extremely rare case of combined classical and periodontal Ehlers−Danlos syndrome (EDS) with early severe periodontitis and a generalized lack of attached gingiva. A German family with classical EDS was investigated by physical and dental evaluation and exome and Sanger sequencing. Due to the specific periodontal phenotype in the affected child, an additional diagnosis of periodontal EDS was suspected. Physical and genetic examination of two affected and three unaffected family members revealed a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Polymorphisms of BRAF V600E and TNSALP, autosomal genetic variation and some other syndromes are common factors for early-onset periodontitis (Table 1). [20][21][22][23][24][25][26][27][28][29] Nonetheless, we commonly ignore the roles of nutrition in the onset and development of periodontitis. In this case, the patient's systemic examination report showed deficient vitamin D levels with no other abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms of BRAF V600E and TNSALP, autosomal genetic variation and some other syndromes are common factors for early-onset periodontitis (Table 1). [20][21][22][23][24][25][26][27][28][29] Nonetheless, we commonly ignore the roles of nutrition in the onset and development of periodontitis. In this case, the patient's systemic examination report showed deficient vitamin D levels with no other abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Qi [16] 2021 Vitamin D deficiency 5 Movement and loss of partial teeth and deep periodontal pockets of remaining teeth Low vitamin D level Deciduous Vitamin D receptor gene mutant Stock [24] 2021 Ehlers-Danlos Syndrome 5 Severe gingival recession and significant alveolar bone loss Joint hypermobility, skin hyperextensibility and connective tissue fragility Deciduous Autosomal dominant genetic Chew [26] 2020 Maturity onset diabetes 21 Multiple periodontal abscesses and severe dental fluorosis…”
Section: Authormentioning
confidence: 99%
“…Two recent pedigree analyses confirm that severe early onset periodontitis is a distinguishing feature between pEDS and classical EDS (cEDS) or vascular EDS (vEDS). In one case, a child with cEDS displayed periodontal bone loss in the primary dentition and a gingival phenotype specific for pEDS (Stock et al, 2021 ). The genetic analysis elucidated two pathogenic mutations, a COL5A1 mutation causative of cEDS together with a de novo C1R mutation causative of pEDS.…”
Section: The Ehlers‐danlos Syndromesmentioning
confidence: 99%
“…Since the first reports of pEDS in the 1970s (McKusick, 1972 ; Stewart et al, 1977 ), 38 case reports/series, seven pedigree analyses and two cohort studies describing a total of 165 individuals have been published (Cortés‐Bretón Brinkmann et al, 2021 ; Kapferer‐Seebacher et al, 2017 , 2019 ; Wu et al, 2018 ; Seo et al, 2019 ; El Chehadeh et al, 2021 ; Stock et al, 2021 ; Nakajima et al, 2022 ). Importantly, all authors reported severe periodontitis as a major criterion of pEDS.…”
Section: Introductionmentioning
confidence: 99%